Exploring Motivation and Challenges in Online Learning: Insights from English Students at One Islamic University in Indonesia - Habibullah, Habibullah; Masbirorotni, Masbirorotni; Haryanto, Eddy (Universitas Jambi, Magister Program of English Education Department, 2024)
The rapid advancement of technology has revolutionized education, leading to the widespread adoption of online learning platforms. Understanding the motivations and challenges faced by students engaged in online learning is essential in this evolving landscape. This research delves into the current phenomena of motivation and challenges in online learning, focusing specifically on the English department at One Islamic University in Indonesia. Through interviews with fourth-semester English students, valuable insights are gained regarding the factors that influence student motivation and the various challenges encountered in the online learning environment. The findings highlight a prevailing sense of boredom and disinterest among some students, stemming from monotonous material, difficulties in understanding lectures, and the lack of direct interaction with instructors. Furthermore, limitations inherent in online learning, such as poor internet connectivity and reliance on digital devices, impede engagement. Qualitative methods shed light on the importance of creating a supportive learning environment, addressing interaction and comprehension challenges, and leveraging external motivators to enhance student engagement and motivation in online learning. The research outcomes provide valuable guidance for educators and institutions seeking to optimize the online learning experience and foster academic success within the English department at One Islamic University in Indonesia.